Increasing young women's knowledge of early marriage issues through audiovisual media intervention - Ega Ersya Urnia; Dini Indo Virawati; Cristinawati B.R. Haloho (PAGEPress Publications, 2023)
Each year, approximately 12 million girls worldwide enter into marriage before reaching the age of 18. In East Kalimantan Province, data from the 2020 National Socio-Economic Survey revealed that 11.54% of women aged 20-24 had experienced early marriage, surpassing Indonesia's average. This study aimed to assess the efficacy of audiovisual and printed health education media in enhancing the knowledge of young women about early marriage. A quasi-experimental approach was adopted, involving 32 young women aged 15-18 from a public high school in Borneo. The study measured the knowledge change in young women and their parents through questionnaires. Data analysis consisted of descriptive and inferential procedures, including normality tests, homogeneity tests, paired t tests, and analysis of variance tests. The findings demonstrated that audiovisual media significantly improved young women's awareness of early marriage (p<0.005). The study encourages midwives and healthcare professionals to employ effective health education media, particularly audiovisual tools, in educational settings to combat early marriage practices.